Sonic writing : technologies of material, symbolic, and signal inscriptions - Magnusson, Thor (Bloomsbury Academic, 2019)
"Sonic Writing explores how contemporary music technologies trace their ancestry to previous forms of instruments and media. Studying the domains of instrument design, musical notation, and sound recording under the rubrics of material, symbolic, and signal inscriptions of sound, the book describes how these historical techniques of sonic writing are implemented in new digital music technologies. With a scope ranging from ancient Greek music theory, medieval notation, early modern scientific instrumentation to contemporary multimedia and artificial intelligence, it provides a theoretical grounding for further study and development of technologies of musical expression. The book draws a bespoke affinity and similarity between current musical practices and those from before the advent of notation and recording, stressing the importance of instrument design in the study of new music and projecting how new computational technologies, including machine learning, will transform our musical practices. Sonic Writing offers a richly illustrated study of contemporary musical media, where interactivity, artificial intelligence, and networked devices disclose new possibilities for musical expression. Thor Magnusson provides a conceptual framework for the creation and analysis of this new musical work, arguing that contemporary sonic writing becomes a new form of material and symbolic design--one that is bound to be ephemeral, a system of fluid objects where technologies are continually redesigned in a fast cycle of innovation."--Publisher's description.